Conservative Narrative: Contemporary Neo-Ottomanist Approaches in Turkish Politics. Issue 3 (2nd July 2020) - Uzer, Umut
Abstract: Turkish politicians, intellectuals and ordinary citizens usually take an ambivalent view of the Ottoman state. The founding fathers of Turkey, mostly soldiers and bureaucrats in the Ottoman state structure had, for the most part, negative perceptions owing to the loss of territory and defeats during the latter days of the Ottoman Empire. Consequently, republican Turkey endeavored to create a modern Turkish nation that was very much part of Western civilization. Nevertheless, fascination with the Ottoman Empire rose to the fore during the multiparty era of the 1950s and further increased in the 1980s and now under the Justice and Development Party (AKP) government. The AKP leadership has been articulating a new identity and historical perspective to create a new national identity for Turkey. This article analyzes the nostalgia for the Ottoman Empire in Turkish politics by focusing on the conservative ideologue Necip Fazıl Kısakürek (1904–1983), who had a significant impact on the AKP leadership as well as on efforts to create a new post-Kemalist Turkey.